“Las garantías al debido proceso y su influencia en los procedimientos de violencia intrafamiliar.” - Novillo Saltos, Vanessa Carolina (2023)
Ecuadorian legislation is guaranteeing due process in which rights and obligations are determined, which ensure guarantees to the inhabitants, particularly the rights of the parties in cases of intrafamily violence. It considers how the non-appearance of the legal medical expert in domestic violence trials violates the Constitutional principle of Due Process. The research modality will be under a mixed approach, that is, qualitative and quantitative, the type of research is descriptive, field and exegetical, after having executed the techniques and instruments in the research, I find that the majority of the lawyers surveyed agree that the appearance of the Legal Medical Expert in trials of violence within the family is relevant and transcendental to issue a correct resolution.